2016
DOI: 10.1016/j.ydbio.2016.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Foxf2 is required for secondary palate development and Tgfβ signaling in palatal shelf mesenchyme

Abstract: The secondary palate separates the oral from the nasal cavity and its closure during embryonic development is sensitive to genetic perturbations. Mice with deleted Foxf2, encoding a forkhead transcription factor, are born with cleft palate, and an abnormal tongue morphology has been proposed as the underlying cause. Here, we show that Foxf2(-/-) maxillary explants cultured in vitro, in the absence of tongue and mandible, failed to close the secondary palate. Proliferation and collagen content were decreased in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 64 publications
1
44
0
Order By: Relevance
“…This results in loss of Shh expression in the palatal shelf epithelium and in CPO (Xu et al, 2016). Suggesting a likely parallel mechanism, Nik et al (2016) found that Foxf2 expression regulates TGFβ signaling activity in the cNCC-derived mesenchyme of the secondary palate. Disruption of TGFβ signaling in these cells has been shown to cause defective proliferation, resulting in cleft palate (Iwata et al, 2012).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…This results in loss of Shh expression in the palatal shelf epithelium and in CPO (Xu et al, 2016). Suggesting a likely parallel mechanism, Nik et al (2016) found that Foxf2 expression regulates TGFβ signaling activity in the cNCC-derived mesenchyme of the secondary palate. Disruption of TGFβ signaling in these cells has been shown to cause defective proliferation, resulting in cleft palate (Iwata et al, 2012).…”
Section: Discussionmentioning
confidence: 95%
“…While Foxf2 has an intrinsic role in secondary palate development, its role in upper lip development and cleft lip pathogenesis had not been described (Wang et al, 2003;Xu et al, 2016;Nik et al, 2016). We therefore further examined the expression of Foxf2 during upper lip morphogenesis in our mouse model.…”
Section: Identification Of Shh-regulated Genes In Upper Lip Morphogenmentioning
confidence: 99%
“…TFs of note include Hox genes, which direct distal limb (Hoxa11/Hoxd11) and digit development (Hoxa13/Hoxd13) (Fromental-Ramain et al, 1996;Villavicencio-Lorini et al, 2010;Zakany and Duboule, 1999); Prrx1, which is required for early skeletogenesis and modulates limb segment length (Cretekos et al, 2008;ten Berge et al, 1998); Alx4 and Tbx2, which affect limb patterning (Kuijper et al, 2005;Sheeba and Logan, 2017); and Runx2, which is a master regulator of osteoblast differentiation (Komori, 2010). Other transiently upregulated TFs in Regen digits include those involved in ECM organization (Foxf2) (Nik et al, 2016), ossification (Runx3) (Bauer et al, 2015), and angiogenesis (Sox17) (Corada et al, 2013). One downregulated TF linked to positive regulation of cell proliferation, Hmga2, is associated with stem cell self-renewal (Hammond and Sharpless, 2008) and tumorigenesis in various tissues (Pallante et al, 2015).…”
Section: Gene Regulatory Network Reveals Tfs Driving Regenerationmentioning
confidence: 99%
“…[9][10][11][12][13][14] Multiple signaling pathways important for palatogenesis such as FGF, TGF β, BMP, and SHH regulate ECM dynamics during palate development ( Figure 1). [6][7][8][14][15][16][17][18] In this review, we will summarize the dynamic deposition and degradation of ECM during palate development.…”
Section: Introductionmentioning
confidence: 99%